CENP-B box and pJalpha sequence distribution in human alpha satellite higher-order repeats (HOR) - Rosandić, Marija; Paar, Vladimir; Basar, Ivan; Gluncić, Matko; Pavin, Nenad; Pilas, Ivan (Chromosome research, 2006)
Using our Key String Algorithm (KSA) to analyze Build 35.1 assembly we determined consensus alpha satellite higher-order repeats (HOR) and consensus distributions of CENP-B box and pJalpha motif in human chromosomes 1, 4, 5, 7, 8, 10, 11, 17, 19, and X. We determined new suprachromosomal family (SF) assignments: SF5 for 13mer (2211 bp), SF5 for 13mer (2214 bp), SF2 for 11mer (1869 bp), SF1 for 18mer (3058 bp), SF3 for 12mer (2047 bp), SF3 for 14mer (2379 bp), and SF5 for 17mer (2896 bp) in chromosomes 4, 5, 8, 10, 11, 17, and 19, respectively. In chromosome 5 we identified SF5 13mer without any CENP-B box and pJalpha motif, highly homologous (96%) to 13mer in chromosome 19. Additionally, in chromosome 19 we identified new SF5 17mer with one CENP-B box and pJalpha motif, aligned to 13mer by deleting four monomers. In chromosome 11 we identified SF3 12mer, homologous to 12mer in chromosome X. In chromosome 10 we identified new SF1 18mer with eight CENP-B boxes in every other monomer (except one). In chromosome 4 we identified new SF5 13mer with CENP-B box in three consecutive monomers. We found four exceptions to the rule that CENP-B box belongs to type B and pJalpha motif to type A monomers.